Assessment of Dermal Safety of Scutellaria baicalensis Aqueous Extract Topical Application on Skin Hypersensitivity - Kim, Tae-Won; Song, In-Bae; Lee, Hong-Ki; Kim, Myoung-Seok; Ham, Seoung-Ho; Cho, Jung-Hee; Lim, Jong-Hwan; Yun, Hyo-In (Planta Medica, 2013)
Scutellaria baicalensis has been used as a traditional herbal medicine for bronchitis, hepatitis, and allergic diseases. The root of Scutellaria baicalensis contains active flavonoid components, including baicalin, baicalein, wogonoside, and wogonin, which have pharmaceutical properties. In the present study, the antiallergic properties of a standardized aqueous extract of S. baicalensis were evaluated, and the skin toxicity of its dermal application was also determined. The in vivo and in vitro assays were performed by using the β-hexosaminidase assay in rat basophilic leukemia cells (RBL-2H3) and cutaneous skin reaction in BALB/c mice, respectively. In addition, the acute dermal irritation/corrosion test was carried out in New Zealand white rabbits, and the skin sensitization test was conducted by Buhlerʼs method in Hartley guinea pigs to estimate the safety of the standardized aqueous extract of S. baicalensis for topical application. β-Hexosaminidase release in RBL-2H3 was markedly decreased following treatment with the standardized aqueous extract of S. baicalensis. It also ameliorated antigen-induced ear swelling compared with the control group in BALB/c mice. In the toxicological studies, it did not induce any dermal irritation/corrosion in rabbits or skin sensitization in guinea pigs. Although still limited, these results concerning the toxicological effects of S. baicalensis could be an initial step toward the topical application of S. baicalensis extracts on hypersensitive skin.
Keywords: Scutellaria baicalensis; Lamiaceae; topical application; skin hypersensitivity; dermal toxicity; β-hexosaminidase